Climate change mitigation in Chinese megacities: A measures-based analysis of opportunities in the residential sector. (15th December 2016) - He, Qi; Jiang, Xujia; Gouldson, Andy; Sudmant, Andrew; Guan, Dabo; Colenbrander, Sarah; Xue, Tao; Zheng, Bo; Zhang, Qiang
Highlights: A measures-based economic analysis of low carbon opportunities is carried out. CO2 abatement potential exists in the residential sectors of Beijing and Shanghai. There are disparities in the carbon and cost-effectiveness of different measures. More abatement potential in Beijing is largely attributed to climate. Abstract: China's commitment to the UNFCCC to peak its emissions by 2030, or sooner, signaled a long anticipated shift in China's model of development with far reaching consequences. Cities in China, and particularly the residential sector in cities, will be charged with making significant reductions in emissions growth even as rates of urbanization continue to climb. Focusing on Beijing and Shanghai, this paper carries out a measures-based economic analysis of low carbon investment opportunities in the residential sector. Results find significant opportunity: between 2015 and 2030, BAU levels of CO2 emissions could be reduced by 10.2% in Beijing and 6.8% in Shanghai with the adoption of economically attractive low carbon measures. While these headline results underline the case for low carbon investment in the residential sectors of these megacities in China, a closer analysis provides insights for understanding the economics of decarbonisation in cities more generally.